TRANSLATION TECHNIQUE ON CULTURAL TERMS: RONGGENG DUKUH PARUK AND ITS TRANSLATION THE DANCER - Aulia Nisa' Khusnia; Elisa Nurul Laili; Anisah Hanif (Universitas Duta Bangsa Surakarta, 2022)
The goal of this study is to outline the translation strategies used in The Dancer, the translation of Ronggeng Dukuh Paruk. Novel Ronggeng Dukuh Paruk was originally published in Bahasa Indonesia. The Javanese terms found in the novel are essential to reveal further. The translator faces a significant challenge in transferring Javanese cultural terms into English. This research is a descriptive-qualitative study that uses documents in both of the novels as data sources. The documents are a novel entitled Ronggeng Dukuh Paruk and its English translation. The data includes linguistic and statistical data in translation. The linguistic data was collected through data analysis and translation. The result is the use of the techniques such as borrowing, calque, transposition, description, generalization, compensation, and established equivalence are all translation techniques. Borrowing and calque are used to translate words into words, which is a characteristic in translating. Transposition and description are phrase to-phrase translations. For word to phrase, there are description and generalization, as well as phrase to word found in established equivalence technique.